Abdurrahman Wahid, Depth Islam, and Religious Pluralism - Bahri, Media Zainul (Ulumuna, 2015)
This essay elucidates the idea of religious pluralism of Abdurrahman Wahid (1940-2009), a very important figure in the tradition of Indonesian Islam. Wahis’s ideas of religious pluralism is based on what the so-called “Depth Islam” (DI). DI is different from the usual theological dogmas that only contains concepts and structures. DI is not a literal and superficial forms of religion. It is an understanding that goes beyond the literal texts to look for the principles and spirit of religion in appreciating humanity, diversity and peace. DI may have arisen because of the long process of religious internalization within Wahid experiences, but it is also a hybrid form, i.e., it is a result of the process of encountering or learning Wahid’s traditions inter-mingling with cultures of the wider world. DOI: http://dx.doi.org/10.20414/ujis.v19i2.333